THE USE OF INSTRUCTIONAL MATERIALS FOR TEACHERS OPINIONS ON THE DETERMINATION OF VISUAL ARTS LESSONS (THE CASE OF ERZURUM) - Oğuz DİLMAC (Fırat University, 2019)
Visual art lesson is a lesson which is a written and spoken expression and has an opportunity for reflecting the emotions and thoughts of child with composition components such as colour, line, shape. Therefore, necessary features of means used in visual art lesson, are to have opportunity the development of child creativity. The most important duty belongs to visual art teachers. When they design the material, it must not prevent the child’s creativity and it must not encourage the imitation works. In this research used Case Study approach, it is aimed to determine which materials are used in teaching sessions and how often they are used by visual art teachers. The research is carried out using survey and observation techniques on the 32 visual art teachers working in the city center of Erzurum. The data is evaluated relating to their gender, teaching experiences and the type of school they graduated by SPSS program with t-test. It is not determined a meaningful differences between male and female teachers considering their level of using materials whereas a meaningful differences can be observed on behalf of the teachers who graduated from education faculties. However their teaching experiences don’t effect their level of teaching materials usage.